Anti-septic solutions for skin preparation in the care of central-catheter insertion in neonates - Muhd Helmi, Muhd Alwi; Mohd Noor, Norhayati (2019)
Various preparation of skin antisepsis was used to prevent catheter-related blood stream infection (CRBSI) in neonate with central venous catheter (CVC). However, their safety and effectiveness are still uncertain. We assessed the safety and efficacy of different antiseptic solutions in preventing CRBSI and other related outcomes in neonates with CVC including the effects on different subgroups. We searched the Cochrane Central, Epistemonikos, PubMed using keywords and MeSH terms, up to August 2019. We included randomised trials that compared different type of antisepsis. Data were extracted using Cochrane Neonatal Review Group methods. Two authors determined eligibility and risk-of-bias (ROB) of the trials. Results were presented in risk ratio (RR) with 95% confidence intervals (CIs). 2 studies involved 352 neonates were included. Both trials compare 2% chlorhexidine in alcohol (CHD/A) and 10% povidone-iodine (PI). Included studies have mixed ROB. Certainty of evidence was mixed for the major outcomes. There is no significant difference in the risk of CRBSI (RR1.28, 95% CI 0.54 to 3.01), clinical sepsis (RR 0.98, 95% 0.56 to 1.71) and skin irritation (RR 1.04, 95% CI 0.24 to 4.48) between CHD/A and PI. All CHD/A-induced skin irritation occurred on infant less than 28 weeks. There was a significant difference in risk of thyroid disorder (RR 0.05, 95% CI 0.00 to 0.85) favouring CHD/A. There were no clear differences in risk of major outcomes like CRBSI, clinical sepsis and skin irritation between CHD/A and PI. However, the use of PI significantly increases the risk of thyroid dysfunction and should be avoided.